2019
DOI: 10.3390/ijms20235998
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs and Novel Food Compounds Related to the Browning Process

Abstract: Obesity prevalence is rapidly increasing worldwide. With the discovery of brown adipose tissue (BAT) in adult humans, BAT activation has emerged as a potential strategy for increasing energy expenditure. Recently, the presence of a third type of fat, referred to as beige or brite (brown in white), has been recognized to be present in certain kinds of white adipose tissue (WAT) depots. It has been suggested that WAT can undergo the process of browning in response to stimuli that induce and enhance the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 235 publications
(217 reference statements)
0
4
0
Order By: Relevance
“…There are a number of published studies showing the health benefits induced by the “browning” of white adipose tissue [ 52 , 53 , 54 , 55 ]. In addition, there are published studies of Omega-3 fish oil converting WAT to beige fat [ 56 ] and even novel food compounds assisting in the browning of WAT [ 57 ]. Our group has focused on the upregulation of heme oxygenase by eicosanoids in vivo [ 3 , 58 ] and in vitro [ 44 ], which has been very effective in the conversion of WAT to beige fat as well as the amelioration of NAFLD and NASH in the liver [ 5 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of published studies showing the health benefits induced by the “browning” of white adipose tissue [ 52 , 53 , 54 , 55 ]. In addition, there are published studies of Omega-3 fish oil converting WAT to beige fat [ 56 ] and even novel food compounds assisting in the browning of WAT [ 57 ]. Our group has focused on the upregulation of heme oxygenase by eicosanoids in vivo [ 3 , 58 ] and in vitro [ 44 ], which has been very effective in the conversion of WAT to beige fat as well as the amelioration of NAFLD and NASH in the liver [ 5 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In adipose tissues, miRNAs play an important role in regulating the pathways that control a range of processes including adipocyte differentiation, insulin signaling and glucose homeostasis (8). Recent studies have demonstrated that some miRNA directly target and regulate thermogenic genes of brown adipocyte development and the beiging of white adipocytes (9)(10)(11). Among adipose expressed miRNA, miR-182-5p is highly enriched in differentiated brown adipocytes compared to non-differentiated cells (12).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that white adipose tissue (WAT) could enhance thermogenesis by the process of ‘browning’. MiRNAs also modulate brite/brown adipogenesis [ 67 ], intriguingly, in which regulatory miRNAs are almost encompassed in breast cancer-associated miRNA list. It suggests that adipose tissue regulation and breast cancer have specific similarity at regulatory miRNA level.…”
Section: Discussionmentioning
confidence: 99%